A revised check-list of the seaweeds of Britain. (29th October 2015) - Brodie, Juliet; Wilbraham, Joanna; Pottas, Jane; Guiry, Michael D.
Abstract : A revision of the check-list of the red (Rhodophyta), green (Chlorophyta) and brown (Ochrophyta, Phaeophyceae) seaweeds of Britain has been compiled and revealed 644 taxa, mostly at species level but including infraspecific taxa: 348 reds, 110 greens and 186 browns. There were 30 additions to the list, notably five newly described species and five new non-native additions. In addition to the check-list, an updated list of non-native species was compiled based on a stringent review of the available evidence. We have listed 31 non-native species ( 5% of the flora), although the numbers may be considerably higher and probably include species that are effectively naturalized and perceived to be part of the indigenous flora. The check-list is discussed in relation to the impact of molecular techniques on the identification, taxonomy and phylogeny of species, and points to the need for a comprehensive, in-depth study on the identity and relationships of the seaweeds of Britain.